2022
DOI: 10.1155/2022/4783994
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Engagement to Academic Tasks: Design and Validation of the Comp-TA Questionnaire

Abstract: This study analyzes the psychometric properties of the engagement to academic tasks (Comp-TA) questionnaire. Rigorous criteria were considered in its design and validation, such as theoretical review, expert judgment, pilot test, and exploratory and confirmatory factor analysis. The instrument was administered face-to-face and in remote modality to a convenience sample of 563 high-school students from schools in Concepción, Chile. The analyses showed a latent structure with a good fit to the data, consisting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
3
0
3
Order By: Relevance
“…An alternative definition of engagement was provided by Krause [20], who argued that engagement comprises the energy, time, and resources used for activities to increase learning at the university. Subsequently, the focus of research began to move to student behavior during classroom tasks and participation in academic work [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative definition of engagement was provided by Krause [20], who argued that engagement comprises the energy, time, and resources used for activities to increase learning at the university. Subsequently, the focus of research began to move to student behavior during classroom tasks and participation in academic work [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Por otro lado, los resultados obtenidos apoyan la estructura factorial original, se identificó un modelo tridimensional similar al propuesto por Yévenes-Márquez et al (2022), Fredricks et al (2004) y Tannoubi et al (2023. Estos resultados reafirman la importancia de estudiar el engagement teniendo en cuenta la interacción de estas dimensiones, pues permiten estudiar el grado de intensidad y la duración que una conducta tendrá en el contexto académico (Freiberg-Hoffmann et al, 2022).…”
Section: Discussionunclassified
“…El engagement vinculado a las tareas y actividades del aula se define como un conjunto de comportamientos favorables por parte de los estudiantes, como el esfuerzo, el entusiasmo y la iniciativa (Jang et al, 2016). De esta manera, Yévenes-Márquez et al (2022) diseñan Ricardo Navarro, Francisco Morote, Arlis García, Víctor Bernal y Victoria Teran ______________________________________________________________________________________________ el instrumento Engagement to Academic Tasks Questionnaire (Comp-TA) con tres dimensiones: cognitiva, conductual y afectiva. En primer lugar, la dimensión cognitiva se entiende como la inversión y el esfuerzo del estudiante en sus estudios.…”
unclassified
“…The emotional dimension refers to the presence of higher levels of sense of belonging and lower levels of anxiety. Finally, the cognitive factor integrates psychological investment, self-regulation and the use of strategies to achieve desired outcomes (Bedenlier et al, 2020;Yévenes-Márquez et al, 2022). Furthermore, the questionnaire shows adequate psychometric properties in a sample of Peruvian university students (χ2(df) = 202.435(87), p < 0.001; S-Bχ2 = 1.383, CFI = 0.924, TLI = 0.908, RMSEA = 0.067 and confidence interval = 0.057-0.077, SRMR = 0.056).…”
Section: Instrumentsmentioning
confidence: 99%
“…and c) the cognitive factor which integrates psychological investment, self-regulation and the use of strategies that are relatively elaborated to achieve the desired results. It is a pending task to develop an instrument to measure academic engagement from the activities and tasks addressed in the classroom that reflects the three dimensions present in Fredricks et al's (2004) model: behavioral, cognitive and emotional considering that researchers should be clear about how they define engagement (Bedenlier, Bond, Buntins, Zawacki-Richter, & Kerres, 2020;Yévenes-Márquez, Badilla-Quintana, & Sandoval-Henrıquez, 2022). Emamjomeh, Toghyani, & Bahrami, 2021;Kowitlawakul et al, (2022) have shown evidence of the predictive power of engagement on performance as well as the direct relationships between engagement and academic achievement and perceived learning effectiveness (Abukhalil, Halawani, & Daher, 2021;Chauhan, Gupta, Palvia, & Jaiswal, 2021;Kala & Chaubey, 2023).…”
Section: Introductionmentioning
confidence: 99%